Beyond the "Sermo modernus": sermon form in early fifteenth-century England - Wenzel, Siegfried (Studies and texts, 2021)
Critiquing the sermo modernus -- Biblical commentary versus sermon cycle -- The sermones super evangelia dominicalia by Repingdon -- Congesta -- Lecturing on sermons -- Sermons in the wake of Repingdon -- Individual preachers -- Innovation? Appendices A: Nicholas Gorran, Commentary and Sermons -- B: Repingdon, Sermon 35 -- C: M, Sermon 37 -- D: Congesta, Sermon 18 -- E: Lecture for the Feast of St Andrew -- F: John Waldeby, Sermon 28.